ショウワ キチ アイスランド キョウヤク テン カンソク ノ ゲンザイ テキ イギ ト ショウライ ケイカク - 佐藤, 夏雄; サトウ, ナツオ; Sato, Natsuo (1989)
P(論文) オーロラ現象の共役性・非共役性の観測や研究は, オーロラを発生させる荷電粒子の加速機構やプラズマ波動の発生・伝搬特性を探る上で重要な課題である。昭和基地-アイスランド共役点対は, 地球上の全オーロラ帯に唯一の貴重な観測点である。この恵まれた条件を活用した諸観測研究は1977年より開始され, 現在も発展的に継続されている。この論文ではこの共役点観測で得られた研究成果をまとめ, さらに, 磁気圏物理学上の問題点を解決するための展望と具体的な観測計画を提案する。 Conjugacy and non-conjugacy of auroral phenomena give us useful information on the acceleration mechanisms for auroral particles and on the generation and propagation mechanism for ULF-VLF waves. However, there have been few conjugate pair of observatories in the northern and southern polar regions. Fortunately, the conjugate point of Syowa Station in Antarctica is located in Iceland. The first conjugate campaign was carried out in 1977,1978,and the second campaign started in 1983 in a more extended scale. This paper summarizes, some significant results for the magnetospheric physics obtained through the conjugate observation, along with a proposal of the future plan. departmental bulletin paper